Group-based Tai Chi as therapy for alleviating experiences of social death in people with advanced, incurable disease: an ethnographic study. Issue 1 (2nd January 2022) - Bradshaw, A; Walker, L; Borgstrom, E; Burke, S.M.
ABSTRACT: Advanced, incurable disease is a highly stressful and traumatic life event that can lead to losses of social identity, social connectedness, and losses associated with bodily disintegration. The combination of these losses makes it difficult to remain socially active and sometimes results in experiences of social death. However, few studies have explored the role of group-based hospice activities for mitigating the impact of social death in people with advanced, incurable disease. The aim of this study was to explore the personal and social experiences of participating in hospice-based Tai Chi among people with advanced, incurable disease, including its impact in mitigating experiences of social death. A focused ethnography was used to guide this study. Six months were spent in a local hospice day therapy unit in England collecting data through multiple methods, including 17 semi-structured interviews, 200 hours of participant observation, and informal conversations with 19 participants (15 females; 4 males, aged between 50 and 91). Data were analysed using a thematic framework approach and represented using traditional tales and ethnographic creative non-fictions (CNF). Two main themes were developed: (1) fostering social connections and meaningful support; and (2) the protection of a collective identity. An ethnographic CNF 'moving and being together' presents these themes in evocative, engaging, and accessible ways. Study findings demonstrate the value of group-based Tai Chi for mitigating experiences of social death in people with advanced, incurable disease. Ethnographic CNFs are a valuable way to represent lived experiences of illness in palliative and hospice care populations.